Development of a Spinal Epidural Abscess Masked by Critical Illness. (July 2014) - Chandler, Ben; Francis, James; Harper, Daniel
We describe a case of severe neurological injury secondary to an epidural abscess that developed during the course of critical illness. It was caused by an oesophageal perforation that developed into an invasive abscess while the patient was being treated in the intensive care unit (ICU) for respiratory failure. We discuss spinal epidural abscesses, and the importance of searching for an alternative diagnosis in patients with weakness.